Imaging Spectrum of Unusual Pineal Region Masses: A Short Series of Four Cases - Dhar, Anandamoyee; Jain, Ruchi; Walia, Bipin; Mukherjee, Urmi; Aggarwal, Bharat (Indian Journal of Neurosurgery, 2017)
Pineal tumors are rare intracranial neoplasm with germ cell tumors and pineal parenchymal tumors being the predominant type, seen in 80 to 90% of cases. Only a few cases of glioblastomas have been reported. The incidence of astrocytoma and meningioma is also low in this region. In this article, we will discuss the key imaging features and diagnostic dilemmas in four rare types of pineal region tumors including pineal parenchymal tumor of intermediate differentiation, pineal astrocytoma, falcotentorial junction meningioma, and glioblastoma with subependymal spread.
Keywords: pineal region tumor; glioblastoma of pineal region; pineal astrocytoma